Upaya Eradikasi Stunting Berbasis Social-Ecological Approach di Kelurahan Untia Kota Makassar - Harisa, Akbar; Hastuti, Hastuti; Majid, Abdul; Malasari, Silvia; Permana, Andi Fajrin; Abdullah, Meutiah Mutmainnah; Hardianty, Nita; Dzauqy, Amrun; Sari, Dewi Novita; Yodang, Yodang (Universitas Baiturrahim, 2024)
Kampung Nelayan Untia as a Family Planning (KB) village. It was established in 2016, with most of its residents working as fishermen. Based on the data collected, this village has several cases of stunting. The solution offered is to provide education and counseling in the form of stunting material. The implementation of the Community Service Activity